2016
DOI: 10.1016/j.scitotenv.2015.06.134
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of climate change on flow regime and fish habitat in mountain rivers of the south-western Balkans

Abstract: The climate change in the Mediterranean area is expected to have significant impacts on the aquatic ecosystems and particular in the mountain rivers and streams that often host important species such as the Salmo farioides, Karaman 1938. These impacts will most possibly affect the habitat availability for various aquatic species resulting to an essential alteration of the water requirements, either for dams or other water abstractions, in order to maintain the essential levels of ecological flow for the rivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 53 publications
(74 reference statements)
3
46
1
4
Order By: Relevance
“…Other studies have carried out descriptive examinations of change in IHA parameters by climate change and their implications on aquatic organisms (Gibson et al., ). The majority of studies projected an increase in frequency and magnitude of the low flow events or drought (Guse et al., ; Papadaki et al., ; Paparrizos & Matzarakis, ), but this study found a contrary situation. This is not surprising as climate projections and their impacts are region‐specific and each generation of climate models or emission scenarios can potentially suggest a different future.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Other studies have carried out descriptive examinations of change in IHA parameters by climate change and their implications on aquatic organisms (Gibson et al., ). The majority of studies projected an increase in frequency and magnitude of the low flow events or drought (Guse et al., ; Papadaki et al., ; Paparrizos & Matzarakis, ), but this study found a contrary situation. This is not surprising as climate projections and their impacts are region‐specific and each generation of climate models or emission scenarios can potentially suggest a different future.…”
Section: Discussioncontrasting
confidence: 62%
“…The SWAT model has been used in combination with the Indicators of Hydrologic Alteration (IHA) methodology (Richter, Baumgartner, Braun & Powell, ; Richter, Baumgartner, Powell & Braun, ) to assess climate change impact on a single fish species habitat suitability by Morid, Delavar, Eagderi and Kumar () and Papadaki et al. (). The IHA consists of 33 parameters that describe the hydrological regime as: magnitude, timing, frequency, duration and rate of change (The Nature Conservancy ).…”
Section: Introductionmentioning
confidence: 99%
“…In mountain rivers of the southwestern Balkans in Europe, due to decreases in summer precipitation and increases in air temperature, minimum flows are projected to decline in the mid‐ and late‐21st century, particularly under the high emission scenario, increasing the risk of droughts (Papadaki et al. ). In a study of the influence of drought on national forests and grasslands across the United States, Sun et al.…”
Section: Effects Of Climate Change On Wes In the Mediterranean Climatmentioning
confidence: 99%
“…In southwestern Balkan mountain rivers in southern Europe, with declines in summer flow and rising stream temperatures, the western Balkan trout population and other biota are projected to decline substantially in the latter half of the 21st century (Papadaki et al. ). Similarly, as a result of decreased flow (20%–29%) and increased water temperature (4–4.2°C), habitat suitability for large brown trout is also projected to decline in the near future (2011–2040) in the Cabriel river in Iberian Peninsula (Muñoz‐Mas et al.…”
Section: Effects Of Climate Change On Wes In the Mediterranean Climatmentioning
confidence: 99%
“…Still higher levels of complexity can be achieved by including a hydraulic model in the modelling chain, but such approaches are typically applied only at small catchment scales (Guse et al, ; Papadaki et al, ). Guse et al () reported variable changes in habitat suitability for fishes in a small stream in northern Germany in response to increased occurrence of seasonal habitat deficits.…”
Section: Predicting Impact Of Climate Change On Hydrological Regimesmentioning
confidence: 99%